Oscillations of MyoD and Hes1 proteins regulate the maintenance of activated muscle stem cells - Lahmann, Ines (Genes Dev, 2019)
The balance between proliferation and differentiation of muscle stem cells is tightly controlled, ensuring the maintenance of a cellular pool needed for muscle growth and repair. We demonstrate here that the transcriptional regulator Hes1 controls the balance between proliferation and differentiation of activated muscle stem cells in both developing and regenerating muscle. We observed that Hes1 is expressed in an oscillatory manner in activated stem cells where it drives the oscillatory expression of MyoD. MyoD expression oscillates in activated muscle stem cells from postnatal and adult muscle under various conditions: when the stem cells are dispersed in culture, when they remain associated with single muscle fibers, or when they reside in muscle biopsies. Unstable MyoD oscillations and long periods of sustained MyoD expression are observed in differentiating cells. Ablation of the Hes1 oscillator in stem cells interfered with stable MyoD oscillations and led to prolonged periods of sustained MyoD expression, resulting in increased differentiation propensity. This interfered with the maintenance of activated muscle stem cells, and impaired muscle growth and repair. We conclude that oscillatory MyoD expression allows the cells to remain in an undifferentiated and proliferative state and is required for amplification of the activated stem cell pool.